2010
DOI: 10.1037/a0021387
|View full text |Cite
|
Sign up to set email alerts
|

Tailored versus generic interventions for skin cancer risk reduction for family members of melanoma patients.

Abstract: Background-Improving strategies for risk reduction among family members of patients with melanoma may reduce their risk for melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 36 publications
3
84
0
Order By: Relevance
“…A recent meta-analysis revealed that tailored messages in computer-mediated safer-sex interventions significantly impacted two mediator variables: sexual/condom attitudes and condom self-efficacy (Noar, Pierce, & Black, 2010). For messages promoting skin cancer detection behaviors, Manne et al (2010) observed that tailoring effects were mediated by intentions but not perceived benefits, barriers, or sunscreen self-efficacy. Most relevant to the present study, Updegraff et al (2007) found that increased message scrutiny and a host of message perceptions (persuasiveness, clarity, accuracy, memorability, importance, helpfulness, and usefulness) mediated the relationship between tailored information and flossing behavior.…”
Section: Tailored Communicationmentioning
confidence: 98%
“…A recent meta-analysis revealed that tailored messages in computer-mediated safer-sex interventions significantly impacted two mediator variables: sexual/condom attitudes and condom self-efficacy (Noar, Pierce, & Black, 2010). For messages promoting skin cancer detection behaviors, Manne et al (2010) observed that tailoring effects were mediated by intentions but not perceived benefits, barriers, or sunscreen self-efficacy. Most relevant to the present study, Updegraff et al (2007) found that increased message scrutiny and a host of message perceptions (persuasiveness, clarity, accuracy, memorability, importance, helpfulness, and usefulness) mediated the relationship between tailored information and flossing behavior.…”
Section: Tailored Communicationmentioning
confidence: 98%
“…They observed an increase in the number of self-reported skin self-examinations by the treatment group (OR, 1.76; 95% CI, 1.06–2.91). Similarly, Manne et al (19) compared a tailored phone and print intervention to generic phone and print interventions among first-degree relatives of melanoma patients. They found that those randomized to the tailored intervention reported significantly greater sun protection habits and were almost twice as likely to have a total skin examination by a doctor.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals in a comparison group received the same educational information but not tailored to their responses and risk profile. The tailored intervention led to improvements in sun protection and total body skin exam (TBSE) behaviors assessed 12 months later, but no changes in self-skin exam (SEE) frequency when compared with the untailored intervention participants (Manne et al, 2010). …”
Section: Hereditary Melanoma Risk Communication With Adult Populationsmentioning
confidence: 99%
“…These interventions have typically included education on the individual’s elevated risk for melanoma. For example, some interventions have targeted unaffected individuals who have a first-degree relative with a history of melanoma (Geller, Emmons, et al, 2006; Manne et al, 2010). In one randomized trial, unaffected family members received information on their skin cancer risk and recommended preventive behaviors tailored to their personal risk characteristics, demographic characteristics (e.g., age, gender), and reported barriers to implementing preventive behaviors.…”
Section: Hereditary Melanoma Risk Communication With Adult Populationsmentioning
confidence: 99%